Utilizing The International Phonetic Alphabet to Improve Pronunciation of English Education Students - Suryaleksana, Blasius Banu; Sari, Margareta Novita; Nadilia, Maria; Bram, Barli (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This paper aimed to discover the effects of the International Phonetic Alphabet (IPA) symbols, consisting of 44 sounds, on pronunciation, the challenges that the English education students face in learning phonetic symbols and the causes of such challenges and students’ steps to improve their pronunciation. The data of this survey study were collected using Google Forms containing an eight-item questionnaire and involved 23 English education students of Sanata Dharma University, Yogyakarta. The results showed the IPA had effects and played an important role in learning phonetics to improve pronunciation, some consonant, vowel and diphthong sounds, such as /θ/, /dʒ/, /ð/, /ɜ:/, and /əʊ/, were challenging to pronounce and the causes included rarely paying attention to the IPA and lacking IPA knowledge. To conclude, it is feasible for the students to learn the IPA to improve their English pronunciation.